Bile Salt-Stimulated Lipase from Human Milk Binds DC-SIGN and Inhibits Human Immunodeficiency Virus Type 1 Transfer to CD4(+) T Cells - Naarding, Marloes A. (American Society for Microbiology, 2006)
A wide range of pathogens, including human immunodeficiency virus type 1 (HIV-1), hepatitis C virus, Ebola virus, cytomegalovirus, dengue virus, Mycobacterium, Leishmania, and Helicobacter pylori, can interact with dendritic cell (DC)-specific ICAM3-grabbing nonintegrin (DC-SIGN), expressed on DCs and a subset of B cells. More specifically, the interaction of the gp120 envelope protein of HIV-1 with DC-SIGN can facilitate the transfer of virus to CD4(+) T lymphocytes in trans and enhance infection. We have previously demonstrated that a multimeric Le(X) component in human milk binds to DC-SIGN, preventing HIV-1 from interacting with this receptor. Biochemical analysis reveals that the compound is heat resistant, trypsin sensitive, and larger than 100 kDa, indicating a specific glycoprotein as the inhibitory compound. By testing human milk from three different mothers, we found the levels of DC-SIGN binding and viral inhibition to vary between samples. Using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, Western blotting, and matrix-assisted laser desorption ionization analysis, we identified bile salt-stimulated lipase (BSSL), a Lewis X (Le(X))-containing glycoprotein found in human milk, to be the major variant protein between the samples. BSSL isolated from human milk bound to DC-SIGN and inhibited the transfer of HIV-1 to CD4(+) T lymphocytes. Two BSSL isoforms isolated from the same human milk sample showed differences in DC-SIGN binding, illustrating that alterations in the BSSL forms explain the differences observed. These results indicate that variations in BSSL lead to alterations in Le(X) expression by the protein, which subsequently alters the DC-SIGN binding capacity and the inhibitory effect on HIV-1 transfer. Identifying the specific molecular interaction between the different forms may aid in the future design of antimicrobial agents.